Guidelines for quality control of PET/CT scans in a multicenter clinical study - Hristova, Ivalina (EJNMMI Phys, 2017)
To date, there is no published detailed checklist with parameters referencing the DICOM tag information with respect to the quality control (QC) of PET/CT scans. The aims of these guidelines are to provide the know-how for effectively controlling the quality of PET/CT scans in multicenter studies, to standardize the QC, to give sponsors and regulatory agencies a basis for justification of the data quality when using standardized uptake values as an imaging biomarker, to document the compliance with the imaging guidelines, to verify the per protocol population versus intent to treat population, and to safeguard the validity of multicenter study conclusions employing standardized uptake value (SUV) as an imaging biomarker which is paramount to the scientific community. Following the proposed guidelines will ensure standardized prospective imaging QC of scans applicable to most studies where SUVs are used as an imaging biomarker. The multitude of factors affecting SUV measurements when not controlled inflicts noise on the data. Decisions on patient management with substantial noise would be devastating to patients, ultimately undermine treatment outcome, and invalidate the utility of SUV as an imaging biomarker usefulness. Strict control of the data quality used for the validation of SUV as an imaging biomarker would ensure trust and reliability of the data.